Classical Economics Today Essays in Honor of Alessandro Roncaglia - Corsi, Marcella; Kregel, Jan; D'Ippoliti, Carlo (Anthem Press, 2018)
Classical Economics Today: Essays in Honor of Alessandro Roncaglia is a collection of essays that pays tribute to Alessandro Roncaglia whose research is based on Schumpeter's dictum that good economics must encompass history, economic theory and statistics, and therefore does not generally take the form of elegant formal models that are applicable to all and everything. In this direction, Roncaglia is inspired by the Classical economists of the past and becomes a model for present-day Classical economists. A perceptible family air imbues the essays: all the contributors are friends of Roncaglia and see his personality and his interests as a common point of reference.